(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The purpose of this study was to determine the ethics of the State Civil Apparatus in carrying out public service tasks at the Camba District Office, Maros Regency. The method used in this study is a qualitative method with 7 informants. Data collection techniques using observation, in-depth interviews, and documentation. The results of this study indicate that the ethics of the State Civil Apparatus in the implementation of public services at the Camba District Office, Maros Regency, shows that in terms of equality, it has been implemented without discriminating against the social background of the community, but it is not yet optimal because there are still people who think that if they want to take care of the files it is necessary acquaintances who work in the office in order to get management faster. Loyalty, in this case, employees are obedient and loyal to the rules, leaders, and co-workers. The responsibilities given in public services are still not optimal, regarding employees at the Camba District Office there are still those who don’t arrive on time so that sometimes hampers services.